The Effect of Human Resource Development and Self-Motivation on Nurse Performance at Solok Selatan Hospital - Niko Mardiansyah; Eva Suryani; Isyuliardi Maas; Dakhyar Dakhyar; Mandra Adrika Putra (Strata Business Review, 2023)
This study consists of 3 variables, namely Human Resource Development (X1), Self-Motivation (X2) and performance (Y). This research is in the form of descriptive quantitative. The population in this study were nurses at Solok Selatan Hospital. The sampling technique used was a questionnaire and documentation with a sample of 71 nurses at Solok Selatan Hospital. To obtain valid and reliable instruments, validity and reliability tests were carried out. The data analysis technique used was multiple regression analysis with the SPSS four windows 25 computer program. The results of this study indicate that (1) the human resource development variable at Solok Selatan Hospital is in the good category with an average score of 4.61 with an achievement level of 92.21%. (2) The variable of Self-Motivation at Solok Selatan Hospital is in the good category with an average score of 4.32 with an achievement level of 86.6%. (3) Performance variables at Solok Selatan Hospital are in the good category with an average score of 4.43 with an achievement level of 87.88%. Simultaneously HR Development and Self-Motivation have a significant effect on performance nurse at Solok Selatan Hospital.